Unveiling a hidden trap: a case of unexpected acardiac twin diagnosed at cesarean section - Vilkhu, Navpreet K.; Tilve, Arundhati G.; Patil, Kartik S.; Shete, Dipti D.; Kore, Shailesh J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Twin reversed arterial perfusion (TRAP) sequence is a rare complication of monochorionic twin pregnancies, occurring in 1 in 35,000 births. It is characterized by retrograde arterial perfusion of a malformed acardiac twin by the structurally normal pump twin through placental vascular anastomoses. A 29-year-old primigravida with a monochorionic diamniotic twin pregnancy was diagnosed with a viable Twin A and intrauterine foetal demise of Twin B on early ultrasonography. Serial scans showed progressive anomalies in Twin B, including a large anechoic cranial cyst, overlapping skull bones and diffuse subcutaneous edema. At 28 weeks of gestation, the patient presented with preterm premature rupture of membranes. An emergency caesarean section was performed for cord presentation of Twin A. A 770-gram male twin were delivered and required intensive neonatal support but died on day 2 of life due to multiorgan failure, birth asphyxia and very low birth weight. The acardiac twin weighed 2390 grams with well-formed lower limbs but severely malformed upper body structures. TRAP sequence results from deep placental arterial-to-arterial anastomoses causing reversed blood flow and variable maldevelopment of the acardiac twin. Pump twins, though anatomically normal, are at significant risk of cardiac overload and poor perinatal outcome, especially when the acardiac twin exhibits disproportionately large mass. Minimally invasive foetal therapies such as radiofrequency ablation and high-intensity focused ultrasound have shown improved survival in selected pregnancies. TRAP sequence remains a rare but serious complication with high morbidity and mortality. Early detection, multidisciplinary counselling and consideration of foetal therapy are crucial for optimizing pump twin outcomes.